Association Between Sleep and Physical Function in Older Veterans in an Adult Day Healthcare Program. Issue 8 (22nd July 2015) - Song, Yeonsu; Dzierzewski, Joseph M.; Fung, Constance H.; Rodriguez, Juan C.; Jouldjian, Stella; Mitchell, Michael N.; Josephson, Karen R.; Alessi, Cathy A.; Martin, Jennifer L.
Abstract : Objectives: To examine whether sleep disturbance is associated with poor physical function in older veterans in an adult day healthcare (ADHC) program. Design: Cross‐sectional. Setting: One ADHC program in a Veterans Affairs Ambulatory Care Center. Participants: Older veterans (N = 50) enrolled in a randomized controlled trial of a sleep intervention program who had complete baseline data. Measurements: Information on participant characteristics (e.g., age, depression, relationship to caregiver, pain, comorbidity) was collected using appropriate questionnaires. Physical function was measured using activity of daily living (ADL) and instrumental ADL (IADL) total scores from the Older Americans Resources and Services Multidimensional Functional Assessment Questionnaire. Sleep was assessed subjectively (Pittsburgh Sleep Quality Index, Insomnia Severity Index) and objectively (wrist actigraphy). Results: Participants required substantial assistance with ADLs and IADLs. A regression model showed that participant characteristics (marital status, use of sleep medication, comorbidity, posttraumatic stress disorder) and living arrangement (living with a spouse or others) were significantly associated with poor physical function. Poorer objective sleep (total sleep time, total numbers of awakenings, total wake time) was significantly associated with poor physical function, accounting for a significant proportion of the variance other than participant characteristics. Conclusion: Objective measures of nighttime sleep disturbance were associated with poor physical function in older veterans in an ADHC program. Further research is needed to determine whether interventions to improve sleep will delay functional decline in this vulnerable population.